Masked Thinkers? Politics and Ideology in the Contemporary Superhero Film - Rodrigo Muñoz-González (KOME: An International Journal of Pure Communication Inquiry, 2017)
This article analyzes the ideological representations in the discourse of contemporary superhero films. In recent years, there has been a tendency in the genre: The characters have become more self-conscious of their roles, even questioning the ‘greater good’ that they are trying to achieve. Thus, the ideological representations of two recent superhero films are studied. For the corpus of analysis, Iron Man (2008) and Captain America: The Winter Soldier (2014) would be selected to be examined based on a Critical Discourse Analysis approach, and using two categories: plot and characters (the second with two subcategories: biographic origin and objectives). The main results point out political contradictions at the discursive level and suggest a relation with current political issues of the contemporary capitalism. This work discusses how a text unfolds an ideology harbored in the meanings and values of an American-based production and political culture.